Protective effects elicited by cow milk fermented with L. Paracasei CBAL74 against SARS-CoV-2 infection in human enterocytes. (December 2021) - Paparo, Lorella; Bruno, Cristina; Ferrucci, Veronica; Punto, Erika; Viscardi, Maurizio; Fusco, Giovanna; Cerino, Pellegrino; Romano, Alessia; Zollo, Massimo; Berni Canani, Roberto
Graphical abstract: Highlights: Fermented foods have been proposed in limiting SARS-CoV-2 infection. Cow's milk fermented with the probiotic L. paracasei CBA L74 modulates a number of protective actions against infections. FM-CBAL74 reduces SARS-CoV-2 entry into host cell and cytokines storm. FM-CBAL74 may be an innovative nutritional strategy to mitigate the COVID-19. Abstract: Fermented foods have been proposed in limiting SARS-CoV-2 infection. Emerging evidence suggest the efficacy of cow's milk fermented with the probiotic L. paracasei CBAL74 (FM-CBAL74) in preventing infectious diseases. We evaluated the protective action of FM-CBAL74 against SARS-CoV-2 infection in human enterocytes. Relevant aspects of SARS-CoV-2 infection were assessed: infectivity, host functional receptor angiotensin-converting enzyme-2 (ACE2), transmembrane protease serine 2 (TMPRSS2), and pro-inflammatory cytokines expression (IL-6, IL-15, IL-1β, VEGFβ, TNF-α, MCP-1, CXCL1). Pre-incubation with FM-CBA L74 reduced the number of infected cells. The expression of ACE2 and the pro-inflammatory cytokines IL-6, VEGFβ, IL-15, IL-1β was downregulated by the pre-treatment with this fermented food. No effect on TMPRSS2, MCP-1, TNF-α and CXCL1 expression was observed. Modulating the crucial aspects of the infection, the fermented food FM-CBAL74 exerts a preventive action against SARS-CoV-2. These evidence could pave the way to innovative nutritional strategy to mitigate the COVID-19.